2019
DOI: 10.1016/j.conbuildmat.2019.04.137
|View full text |Cite
|
Sign up to set email alerts
|

Combination of superplasticizers with hydroxypropyl guar, effect on cement-paste properties

Abstract: Viscosity-modifying agent (VMA) are used in several applications of concrete, such as underwater concrete, Self-Compacting Concrete (SCC) or Self-Levelling Underlayments (SLU) in order to improve the washout resistance and the stability. The study focuses on the modifications of cement pastes properties implied when a VMA (hydroxypropyl guars or HPG) and a superplasticizer are introduced together. For reaching this objective, two chemically different polycarboxylate-based superplasticizers (PCE) and two HPGs e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…However, the combination of several admixtures in cement paste may cause undesired interactions. Indeed, competitive adsorption between these admixtures on the surface sites of cement particles may occur, which may influence their performances [43][44][45]. When combining PCE with sodium gluconate (NG) or with hydroxyethyl cellulose (HEC), Bessaies-Bey et al [44] found that NG is able to fully desorb the pre-adsorbed PCE while PCE was also able to fully desorb the pre-adsorbed HEC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the combination of several admixtures in cement paste may cause undesired interactions. Indeed, competitive adsorption between these admixtures on the surface sites of cement particles may occur, which may influence their performances [43][44][45]. When combining PCE with sodium gluconate (NG) or with hydroxyethyl cellulose (HEC), Bessaies-Bey et al [44] found that NG is able to fully desorb the pre-adsorbed PCE while PCE was also able to fully desorb the pre-adsorbed HEC.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this competitive adsorption between these admixtures, the yield stress and viscosity of the paste were decreased. In addition, Govin et al [45] highlighted a decrease of the dispersing effectiveness of PCE when combined with hydroxypropyl guar (HPG). The authors demonstrated that the admixtures (PCE and HPG), which were introduced at the same time, competed for adsorption, which explains the decrease of the yield stress of the paste.…”
Section: Introductionmentioning
confidence: 99%
“…Bessaies-Bey et al [18] showed that PAM microgels can be adsorbed on cement particles concurrently to establish bridges between them, thereby increasing the macroscopic yield stress. With respect to the increased viscosity and yield stress owing to the viscosity modifying agents, the polycarboxylate superplasticizer (PCE) can be adopted to regulate the workability [19]. Yang et al [16] indicated that the use of superplasticizers in CPB specimens was beneficial in maintaining/improving the workability and strength properties by decreasing water requirements without lowering the fluidity or raising the amount of cement.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [16] indicated that the use of superplasticizers in CPB specimens was beneficial in maintaining/improving the workability and strength properties by decreasing water requirements without lowering the fluidity or raising the amount of cement. Govin et al [19] investigated the effect of PCE and hydroxypropyl guar (HPG) on cement paste properties and showed that the rheological properties of the cement paste were significantly modified when HPG and PCE were combinedly used. Thus, the use of rheological additives should be optimized through a multi-objective approach.…”
Section: Introductionmentioning
confidence: 99%
“…Guar gum improves the water retention of mortar or concrete, adapts the rheological behavior of the cementitious materials, prevents aggregate segregation and improves the workability and homogeneity of cement-based systems. Moreover, the addition of the guar gum slightly increases the strength and reduces the carbonation rate [30,31]. Starches are VMA that alter the properties of a mortar in the fresh state.…”
Section: Introductionmentioning
confidence: 99%